DEVELOPMENT OF AN ISLAMIC RELIGIOUS EDUCATION LEARNING MODEL BASED ON RELIGIOUS MODERATION - Prasetiyo, Nova Tri; Akhyak, Akhyak; Tanzeh, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Developing an Islamic Religious Education (PAI) learning model based on religious moderation is an urgent need in the context of an increasingly plural world. The aim of this research is to formulate an innovative approach to PAI learning that integrates the values of religious moderation, such as tolerance, balance and respect for diversity. This research was conducted using a literature review method, analyzing various previous studies on religious moderation, innovative learning models, and Islamic religious education in various contexts. The results of the study show that learning based on religious moderation is effective in building inclusive attitudes and preventing potential extremism among students. This model emphasizes the use of strategies such as contextual teaching and learning (CTL), problem-based learning (PBL), and integration of learning technology to increase students' understanding of the importance of moderation. The integration of the value of moderation has also been successfully implemented through teaching materials that raise the issue of diversity and the history of tolerance in Islam. Digital media, such as interactive learning platforms and educational videos, have become a significant tool in attracting the attention of the younger generation and strengthening the internalization of the values of moderation. The conclusion of this research states that developing a learning model based on religious moderation is not only important for building inclusive religious competence, but is also relevant in preparing students to face the challenges of the times. It is hoped that this model will be able to create a generation that adheres to religious teachings while respecting social diversity. Further research is needed to test the implementation of this model in various educational contexts